Dream! create! sustain! : mastering the art and science of transforming school systems - Duffy, Francis M. (Francis Martin), 1949- (Leading systemic school improvement., 2010)
This book provides change leaders in education with essential concepts, principles, strategies, and tactics for how to create and sustain whole-system change in their school systems.